Effect of varying pH on solution interactions of soluble meat proteins with different plant proteins. Issue 2 (10th January 2022) - Gibis, Monika; Trabold, Linda; Ebert, Sandra; Herrmann, Kurt; Terjung, Nino; Weiss, Jochen
Abstract : Replacing animal proteins with plant-based proteins is becoming increasingly popular as demand for alternative and more sustainable protein sources increases. Abstract : The exchange of animal-based for plant-based proteins is becoming more and more popular due to an increasing demand for alternative and more sustainable protein sources. In this study, solubilized water- (ws) or salt-and-water (sws) meat proteins were evaluated in their pH-dependent interactions with soluble protein fractions from wheat, pumpkin, sunflower, rapeseed, or potato proteins. For this purpose, 1 : 1 (v/v) mixtures of 1.0 wt% meat (ws or sws) and plant proteins were prepared at a sodium chloride concentration of 1.8 wt% (ionic strength: 0.31 mol L −1 ) and adjusted to different pH-values in between 4.5–7.0. While only slight differences were found upon comparison of interactions of ws and sws batches ( p > 0.05), interactions among these animal-based and soluble plant proteins took place. First, optical observations, light microscopy, and SDS-PAGE revealed increasing protein solubility with increasing pH. Second, particle size distributions (PSDs) revealed a shift towards slightly larger particle sizes e.g. at pH 5.3 and 7.0 with d 4, 3 of 43.2 and 21.3 μm (sws) to 45.4 and 23.9 μm (sws + potato), respectively. Furthermore, heat-induced gel formation was improved at pH > 6.0, in particular in mixtures of meat and wheat or rapeseed proteins that formed a homogenous gel structure. Based on the obtained results, protein–protein complexations mainly by electrostatic forces are suggested which occur due to various pI of meat and plant proteins e.g. pH 7.5 (wheat), 7.2 (potato), and 6.6 (rapeseed) in comparison to 5.1 (ws) and 5.6 (sws). The filamentous microstructure of some gels (soluble fraction of rapeseed, potato and wheat proteins) led to the assumption that meat proteins, mainly at pH values greater than 5.8 (optimally ≥6.5), had a structuring effect on plant proteins.